The influence of excellent service by butler service on guest satisfaction at Tanadewa Villas & Spa - Kadek Intan Diastari Dewi; I Gusti Agung Mas Krisna Komala Sari; Ni Putu Wiwiek Ary Susyarini; Ni Luh Eka Armoni; Dewa Made Suria Antara (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2022)
This research aims to determine the effect of excellent service by butler on guest satisfaction at Tanadewa Villas & Spa. This research used a quantitative method. Data were collected by questionnaire were analyzed using simple linear regression analysis. The collecting of data was an observation, distributed the questionnaire, and interviewing the assistant front office manager. The population in this research was the number of guests who stayed at Tanadewa Villas & Spa for six months from October 2020 to April 2021. The total of samples of this research was 30 respondents. The results of this research 30 respondents stated excellent service by butler has a significant effect and has a positive direction towards guest satisfaction. The Pearson Correlation test results between the excellent service and guest satisfaction variable (Y), which are 0.662, show that the correlation between excellent service and guest satisfaction is high. Determination Coefficient Analysis shows that excellent service has 43.9% in explaining the variance of guest satisfaction, while the remaining 56.1% is from other factors not in this research. All the indicators have shown numbers above four of the Likert Scale. It means excellent service is still needed to optimize to make guest satisfaction such as teaching English of serving guests, providing directions on how to use the facilities in the villa, for example operating coffee machine or EDC machine, and carrying out guidance also socialization periodically focuses on excellent service procedures to butler employees.